Investigating macrophage-lymphatic vessel interactions in neonatal mouse model of heart regeneration - Klaourakis, K (2021)
Myocardial infarction (MI) triggers an immune response, whereby phagocytic cells remove dead tissue and assist with the subsequent remodelling and repair of the infarcted heart. In adult mice, MI activates cardiac lymphatics, which function to drain the build-up of interstitial fluid (oedema) and traffic macrophages to mediastinal lymph nodes (MLNs), reducing inflammatory/fibrotic cell content and improving cardiac output. Mice at postnatal day 1 (P1) fully regenerate their heart following MI in a pro-regenerative macrophage-dependent manner, whereas similar injury at P7 leads to scarring driven by pro-fibrotic macrophages. The role of cardiac lymphatics in the regenerative capacity of neonatal mice remains unexplored. Therefore, we hypothesised that lymphatics respond and function differently following MI during this regenerative window (P1 to P7), to clear macrophage specific subtypes depending upon their requirement for regeneration (P1) or fibrotic repair (P7).